Die Regesten des Kaiserreiches unter Friedrich I. 1152 (1122)-1190 4. Lieferung 1181-1190 - Opll, Ferdinand (2011)
The present publication includes the historical tradition being relevant for the history of the Western medieval empire under the reign of Frederick Barbarossa from 1181 to 1190. Highlights of this decade were the deposition of Henry the Lion (1181), the peace of Constance with the Lombard Communes (1183), the pentecosten-festivities at Mainz (1184), the last sojourn of the Swabian ruler in Italy (1184-1186) with the nuptials of Henry VI with Constance of Sicily in Milan (January 27, 1186), the Diet called "Jesu Christi" at Mainz with the decision to start the crusade (1188) and the crusade itself until the death of the Emperor in the river Saleph (now: Gök-su) on June 10, 1190. The first three volumes - 1122/1152 until 1158 June, 1158 july until 1168 march and 1168 march until the end of the year 1180 - have been published in 1980, 1991 and 2001. Now, after the finalization of vol. 4 a statistical approach towards the whole time of Frederick's government is possible: In doing so it arises that vol. 4 with 892 regesta is taking the second place in the ranking of all 4 volumes (vol. 1: 1217 regesta - vol. 3: 804 regesta - vol. 1: 558 regesta). Although the application of statistical methods to medieval phenomena bears a lot of problems because of the lack of abundant source materials some very important insights are possible: So it can be shown that a high intensity of historical tradition (51-100 regesta per year) can be stated for 18 years of Barbarossa's reign. An extraordinary high intensity of historical tradition can be seen for the years 1162 (173 Regesten), 1167 (155 Regesten), 1159 (154 regesta), 1164 (151 regesta) and 1177 (142 regesta). The overview over the whole reign of the Swabian emperor demonstrates clearly that a high intensity of historical tradition is always connected to the dramatic events of certain years. Best examples are the years of the second, third and fourth sojourn of the Emperor in Italy (1159-1167) with the highly dramatic conflicts with the papcy and the Lombard communes and with the top-rank for 1162 (destruction of Milan). The year 1189, part of the present vol. 4, is absolutely on top with 201 regesta. Nevertheless this position is due to two specific factors: on the one hand all the non-dated Deperdita (lost imperial charters) and other notices are placed just before the start of the crusade, when the emperor left the empire's territory; on the other hand the historical tradition for the crusade itself is of an astonishing abundancy. The indispensability of integrating all the historiographical sources (approximately 60 % of the 3471 regesta are based on them) is one of the great insights after working for 35 years on this project. Only by such an approach a profound documentation for the period of Frederick I is possible.